'A study on the service performance of "on-call-maintenance services" by DiGiCITY (M) Sdn Bhd.' / Mohd Izral Mohd Nazir - Mohd Nazir, Mohd Izral (Faculty of Business and Management, 2002)
Nowadays, as we lived in the 22nd centuries, computers have emerged as one of the important things in our day life. People were using computers to assist them in their work and their task. They are trying to acquire more knowledge and skills of computers in order to make their life easier. Even big companies looked for computers now as their competitive advantage.